Injuries and pathologies in beach volleyball players: A systematic review - Jiménez-Olmedo, J. M.; Penichet-Tomás, A. (Journal of Human Sport & Exercise, 2015)
The aim of this paper is to review the available literature published on injuries and pathology in beach volleyball. The databases consulted were the Web of Sciende and Pubmed. After establishing the criteria for selection and filtering, a total of 32 articles were selected. All items found can be classified into four research lines. First are the studies focused on specific injuries such as shoulder, shoveling, knee and foot. The second line of research focuses on the study of the incidence, prevalence and frequency of injuries of beach volleyball players, whereas the third line deals on infections reported in the literature produced by nematodes or fungi. Finally, the last line of research includes articles addressing different objectives related to health such as the effects of training programs related to injuries, influence of weather conditions on the players, as well as publications for validation of assessment instruments or develop of guidelines and protocols for the evaluation and diagnosis of injuries.